EFFECT OF THE USE OF WOOD CHARCOAL ASH ON THE COMPRESSIVE STRENGTH OF NORMAL CONCRETE - Martin Richardo William; Kristina Sembiring; Sempurna Bangun; Pio Ranap Tua Naibaho (International Journal of Civil Engineering and Infrastructure, 2023)
Wood charcoal ash is the result of chemical changes from the burning of wood. Wood charcoal contains silica which is a good binder aggregate for concrete mixtures, it is the same as the function of cement in a concrete mixture. Wood charcoal can also be used as a mixture or addition to the manufacture of reactive concrete. Concrete is a mixture of portland cement, fine aggregate, coarse aggregate and water, with or without additives that form a solid mass. Concrete is prepared from coarse aggregate and fine aggregate. Cement and water interact chemically to bind the aggregate particles into a solid mass (George Winter, 1993). Based on the results of research that has been done, the results obtained on normal concrete of 17.98 Mpa at the age of 7 days and increased at the age of 14 days of 20.73 Mpa, and 28 days of 22.94 Mpa. At the time of normal concrete mixed with wood charcoal ash 3% compressive strength of concrete again increased by 20.43 Mpa at the age of 7 days, but at the age of 14 days of concrete with a mixture of wood charcoal ash increased by 20.82 Mpa and again increased at the age of 28 days by 27.07 Mpa. The decrease continued to occur in concrete with a mixture of wood charcoal ash 8% and 13% at the age of 7 Days, 14 days, and 28 days, the increase in the compressive strength of the optimal concrete is in the concrete mixture of wood charcoal ash 3% at the age of 28 days.